A hybrid type I, multi-center randomized controlled trial to study the implementation of a method for Sustained cord circulation And VEntilation (the SAVE-method) of late preterm and term neonates: a study protocol - Katarina Ekelöf; Elisabeth Sæther; Anna Santesson; Maria Wilander; Katarina Patriksson; Susanne Hesselman; Li Thies-Lagergren; Heike Rabe; Ola Andersson (BMC Pregnancy and Childbirth, 2022)
Abstract Background An intact umbilical cord allows the physiological transfusion of blood from the placenta to the neonate, which reduces infant iron deficiency and is associated with improved development during early childhood. The implementation of delayed cord clamping practice varies depending on mode of delivery, as well as gestational age and neonatal compromise. Emerging evidence shows that infants requiring resuscitation would benefit if respiratory support were provided with the umbilical cord intact. Common barriers to providing intact cord resuscitation is the availability of neonatal resuscitation equipment close to the mother, organizational readiness for change as well as attitudes and beliefs about placental transfusion within the multidisciplinary team. Hence, clinical evaluations of cord clamping practice should include implementation outcomes in order to develop strategies for optimal cord management practice. Methods The Sustained cord circulation And Ventilation (SAVE) study is a hybrid type I randomized controlled study combining the evaluation of clinical outcomes with implementation and health service outcomes. In phase I of the study, a method for providing in-bed intact cord resuscitation was developed, in phase II of the study the intervention was adapted to be used in multiple settings. In phase III of the study, a full-scale multicenter study will be initiated with concurrent evaluation of clinical, implementation and health service outcomes. Clinical data on neonatal outcomes will be recorded at the labor and neonatal units. Implementation outcomes will be collected from electronic surveys sent to parents as well as staff and managers within the birth and neonatal units. Descriptive and comparative statistics and regression modelling will be used for analysis. Quantitative data will be supplemented by qualitative methods using a thematic analysis with an inductive approach. Discussion The SAVE study enables the safe development and evaluation of a method for intact cord resuscitation in a multicenter trial. The study identifies barriers and facilitators for intact cord resuscitation. The knowledge provided from the study will be of benefit for the development of cord clamping practice in different challenging clinical settings and provide evidence for development of clinical guidelines regarding optimal cord clamping. Trial registration Clinicaltrials.gov, NCT04070560 . Registered 28 August 2019.